NUTRIENT CYCLING IN 2 SOUTH-EAST BRAZILIAN FORESTS .1. LITTERFALL AND LITTER STANDING CROP - Morellato, LPC (Cambridge University Press, 1992)
Litterfall (leaves, woody < 5 cm diameter, flowers and fruits) was estimated monthly using 20 litter traps, each 1 m2 , and litter standing crops were collected every three months using 20 samples of 0.5 m2, for Altitudinal forest (AF) and Semideciduous forest (SF) in south-east Brazil (Serra do Japi, Jundiai, São Paulo State) from March 1985 to March 1986. The total litterfall was 7 t ha-1 y-1 for AF:4.9 leaves, 1.8 woody, 0.13 flower, 0.16 fruits; and the total for SF was 8.6 t ha-1 y-1: 5.5 leaves, 2.1 woody, 0.5 flower, 0.4 fruits. Litter standing crop was 5.5 t ha-1 y-1 for the two forest sites studied with a turnover coefficient (K1) of 1.3 for AF and 1.6 for SF. Litterfall occurred throughout the year but was greater during the dry season (August-September); seasonality of litter and leaf fall was greater in SF than in AF but in both followed the litterfall patterns of other south-east Brazilian forests.
Keywords: ALTITUDINAL FOREST; LITTERFALL; LITTER DECOMPOSITION; LITTER STANDING CROP; SEMIDECIDUOUS FOREST; SOUTH-EAST BRAZIL